LDTtool: A toolbox to assess landscape dynamics. (November 2020) - Machado, Rui; Bayot, Roy; Godinho, Sérgio; Pirnat, Janez; Santos, Pedro; de Sousa-Neves, Nuno
Abstract: The "LDTtool" python toolbox is introduced. This ArcGIS toolbox can be applied to assess land cover or land use changes between two or three moments, considering landscape composition and configuration. The development of LDTtool occurs in a time when the studies on landscape dynamics looking at amount and configuration changes are becoming mainstream. The use of analytical units, whether regular polygons like squares or irregular like districts, allows to study at broad as well as at detailed scales, depending on the base maps spatial resolution and intrinsic quality. The ultimate goal of the toolbox is to assign each analytical unit to a type of dynamic. The paper shows how to operate the toolbox and provides a case study regarding the olive groves dynamics in Portugal in the period 1990–2018. Graphical abstract: Image 1 Highlights: LDTtool is a python-based toolbox to analyse landscape dynamics. Considers landscape composition and configuration. Uses vector binary landscapes. Assigns Types of Dynamics to analytical units.